Delivering behaviour support to children and adolescents with autism via telepractice: a narrative review. Issue 2 (3rd July 2022) - Johnsson, Genevieve; Bulkeley, Kim
Abstract: Access to timely behaviour support services for children and adolescents with a disability in rural and remote regions of Australia is problematic due to the inadequate supply of specialised staff providing complex behaviour support in their local area. Technology has the potential to provide a timely, quality, low-cost option that extends access to behaviour support services for these children and their support teams in rural and remote areas. The purpose of this narrative review was to explore policy and practice guidelines on the delivery of behaviour support via telepractice for children and adolescents with a disability in Australia, and more specifically for those on the autism spectrum. Secondly, the review aimed to establish the evidence base of this model of service for children and adolescents with autism, in order to reflect on how it aligns with current Australian policy and practice. Practice and policy documents were drawn from selected websites relevant to the delivery of behaviour support via telepractice in Australia. Peer-reviewed literature (2004–2019) on the delivery of behaviour support via telepractice was sourced via four databases. While telepractice appears to have promising utility for the provision of support for children and adolescents with autism who present with challenging behaviour, there was very little policy documentation or guidelines found that related specifically to the delivery of this support. There is a need for further rigorous research to inform policy, establish efficacy, and develop practice guidelines that ensure delivery of high quality telepractice behaviour supports under the National Disability Insurance Scheme.